БАЛАЛАР ПСИХОЛОГИЯСЫН РАЎАЖЛАНДЫРЫЎДА ҚАРАҚАЛПАҚ ХАЛЫҚ АЎЫЗ ЕКИ ДӨРЕТПЕЛЕРИНИҢ ТУТҚАН ОРНЫ - Ибрагимова, Л.А. (FAN va JAMIYAT, 2018)
In the article it is broadly revealed the place and importance of children‘s rhymes, fairy-tales, riddles, patters sayings and proverbs samples of Karakalpak folklore in the development of the children‘s psychology. The issue is thoroughly analyzed in the aspects of the history and theory of pedagogics af one of the important problems of pedagogics.